(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Klueva N.Ju. Keywords: lingvopragmatics, fictional text, fictional communication, ad- dressant, addressee, integral constructions, parcelled constructions. The article presents the results of the study of syntactic structures that implement an author’s pragmatic potential in a literary text. The constructions can be of two types, integral and parcelled. The article offers a complex analysis of such syntactic units in order to identify their pragmatic expressive and appellative potential. The author studies them through the pragmatic categories of “addressant-addressee”, “intention”, “illocution”, “perlo- cution”.